Authentic Happiness as a Mediator of Work-Life Balance and Learning Organization on Employees Work Achievement - Antonius Dieben Robinson Manurung; Tika P. Bisono (Bulletin of Counseling and Psychotherapy, 2026)
Human capital management plays a crucial role in enhancing organizational competitiveness and employee performance. Organizations must continuously develop employees’ competencies, capabilities, and well-being to achieve optimal work outcomes. This study examines the role of authentic happiness as a mediator in the relationship between work-life balance and learning organization practices and employee work achievement. The study employed a quantitative research design using Structural Equation Modeling (SEM) to analyze the relationships among variables. Data were collected through a survey questionnaire distributed to 212 employees of PT X in East Kalimantan, Indonesia, selected using purposive sampling. In addition, supporting qualitative insights were obtained through interviews with the Assistant Vice President (AVP) of training to contextualize the organizational environment. The research aims to analyze: (1) the effect of work-life balance on employee work achievement; (2) the effect of learning organization on employee work achievement; (3) the effect of work-life balance on authentic happiness; (4) the effect of learning organization on authentic happiness; and (5) the mediating role of authentic happiness in the relationship between work-life balance, learning organization, and employee work achievement. The findings indicate that work-life balance and learning organization significantly influence employee work achievement, while work-life balance also positively affects authentic happiness. However, authentic happiness does not significantly mediate the relationship between organizational factors and employee work achievement. These findings highlight the importance of organizational policies that promote work-life balance and learning culture to improve employee performance.